Cataract: An Article Review - Irawan, Rocky (Rifa'Institute, 2024)
Introduction: Cataract, the leading cause of global visual impairment, affects over 13 million individuals with blindness, and its prevalence is expected to rise due to population aging and lifestyle changes. Cataracts significantly impact vision, mental well-being, quality of life, and increase mortality rates and economic burdens. Objective: This study reviews the prevalence, risk factors, and treatment outcomes of cataracts, assessing the influence of demographic changes and lifestyle factors on their incidence and progression. Methods: This study reviewed English literature from 2019 to 2024, excluding editorials, reviews from the same journal, and submissions without a DOI. Literature sources included PubMed, SagePub, SpringerLink, and Google Scholar. Results and Discussion: The global prevalence of cataracts increases significantly with age, from 3.9% in individuals aged 55-64 to 92.6% in those aged 80 and above. Cataracts remain a major cause of blindness in low-income countries, accounting for 50% of cases compared to only 5% in developed nations. Cataract types vary, with nuclear cataracts primarily affecting distance vision and posterior subcapsular cataracts impairing near visual acuity. Surgical innovations, such as premium intraocular lenses and femtosecond laser-assisted cataract surgery, enhance outcomes but complications persist. Limited accessibility to cataract surgery in low-income countries remains a significant challenge. Conclusion: Cataracts continue to pose a significant global health burden, particularly in aging populations and low-income regions. Despite advancements in treatment, addressing accessibility and improving surgical outcomes are crucial for reducing cataract-related vision impairment.